Self-Assessment in Exploring EFL Students' Speaking Skill - Alek Alek; Abdul Gafur Marzuki; Muhammad Farkhan; Rahma Deni (State Institute of Islamic Studies Imam Bonjol Padang, 2020)
Self-assessment is one of alternative ways to evaluate students' speaking talent in English. Through this evaluation, students are allowed to discover, know, and develop their speaking skill. Nonetheless, this sort of project was probably not common in Indonesia. Thus, this study was aimed to know students' perception of using self-assessment for assessing their oral performance at Link and Match vocational high school. The information of this study was gathered by means of questionnaire which consists of 5 questions about the use of self-assessment. In this qualitative study, the data had been analyzed descriptively. There have been 30 vocational high school students who stand in Multimedia Major as the participant of this study. The results of this study indicated that most of the students thought that self-assessment very helpful for them because it allowed them to know their functionality and develop it to achieve the course goal specifically the speaking course objective. However, some students though that self-assessment was considerably useful since the teacher not often use this assignment and the students not take pleasure in whereas attempting to assess themselves. Self-assessment is very useful in exploring and assessing students speaking skill.